Samband mellan linjär beskrivning av hoppegenskaper på unghästtest och senare tävlingsprestation hos svenska varmblodiga hästar - Björkman, Viktoria; Norberg, Frida (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2019)
One goal of the association of Swedish Warmblood horses (SWB) is to be internationally competitive in both dressage and show jumping. Since performances at a high level are achieved late in life, selection is often based on information from young horse tests. Earlier studies have shown that there are strong genetic correlations between traits assessed at young horse tests and future competitions results. There are, however, no studies on which detailed jumping traits that are most important for a successful show jumping career for SWB horses. In 2013, SWB introduced a linear description at young horse test where the horses are described for 50 different traits on a linear scale between two extremes (A to I). The aim of this study was to investigate correlations between linearly described jumping traits at three years of age and show jumping competition results later in life. The question at issue was which linear show jumping traits are most important for the young horse to succeed in its future competition career.